Respuesta :

s1m1
(fog)(x)= f(g(x))= 4(x^2-5)+1= (4•x^2)-20+1=

(4•x^2)-19

Answer:

(fog)(x) = [tex]4x^{2}-19[/tex]

Step-by-step explanation:

The given functions are f(x) = 4x + 1 and g(x) = [tex]x^{2}-5[/tex]

We have to find the value of (fog)(x).

Since (fog)(x) = f[g(x)]

It means we have to find the value of f(x) for the value of x = g(x)

Now f[g(x)] = [tex]4[x^{2}-5]+1[/tex]

                 = [tex]4x^{2}-20+1[/tex]

                 = [tex]4x^{2}-19[/tex]

Therefore, f[g(x)] = [tex]4x^{2}-19[/tex] will be the answer.

ACCESS MORE